O contestado entre Santa Catarina e o Paraná : uma questão de limite territorial nos limites da nação - Geller, Odair Eduardo (2010)
Between 1766 and 1916 the territory located between the rivers Iguazu and Uruguay, from Lages to the Argentinean border was the object of Santa Catarina and São Paulo dispute, after 1853 the Parana one. In part, as a consequence of administrative limits undetermined established still in the colonial period, during 150 years the administrative case of one and another litigant were gradually questioned, making that the territory slowly assumed a nobody s land condition. In this meantime, a varied gamma of individuals, most of them from the suburbs of the nucleus of Iberian settling, penetrate in the region giving origin to a society that under the influence of the regional armor, develops its own structure and rhythm, to base its inhabitant s characteristic mentality. This reality, contrary the task that the Brazilian State receives in the moment of its foundation, to forge, among the diversity of origins and cultures, a common basic nucleus capable to create national identity, becomes the "contestado" a nation s cultural border. The resolution of the Limits s Question in the 20th of October of 1916 represented a politician act of extreme conscience about the Brazilian nation s reality. Intervening in the Question, the federal executive made possible the beginning of the process of the region s nationalization through the accurate definition of the jurisdiction from each one of the States. The presence of the ideological State s devices on all the extension of the territory, constitutes in the Brazilian case, the condition "sine qua non" for the production of national identity